Adaptation of Western counselling approaches to an Asian multicultural context - Soong, Cecilia Foong Har. (2009)
This study is focused on worldviews of counsellors and counsellees, and their use of and preference for counselling approaches. In the light of the underlying value differences between Western and Eastern cultures, there is a need for counsellors in an Eastern culture to adapt Western approaches to the local multicultural context. Chapter One discusses the concept of worldview, a significant antecedent factor in counselling, and its correlates. The main premise is that worldviews, encompassing one's 'stock of knowledge', influence one's perceptions of counselling and one's preference for counselling approaches.